DeepATsers: a deep learning framework for one-pot SERS biosensor to detect SARS-CoV-2 virus - Ankhbayar Nyamdavaa; Kiran Kaladharan; Erdene-Ochir Ganbold; Seungdo Jeong; Seonuck Paek; Yansen Su; Fan-Gang Tseng; Tseren-Onolt Ishdorj (Scientific Reports)
Abstract The integration of Artificial Intelligence (AI) techniques with medical kits has revolutionized disease diagnosis, enabling rapid and accurate identification of various conditions. We developed a novel deep learning model, namely DeepATsers based on a combination of CNN and GAN to employ a one-pot SERS biosensor to rapidly detect COVID-19 infection. The model accurately identifies each SARS-CoV-2 protein (S protein, N protein, VLP protein, Streptavidin protein, and blank signal) from its experimental fingerprint-like spectral data introduced in this study. Several augmentation techniques such as EMSA, Gaussian-noise, GAN, and K-fold cross-validation, and their combinations were utilized for the SERS spectral dataset generalization and prevented model overfitting. The original experimental dataset of 126 spectra was augmented to 780 spectra that resembled the original set by using GAN with a low KL divergence value of 0.02. This significantly improves the average accuracy of protein classification from 0.6000 to 0.9750. The deep learning model deployed optimal hyperparameters and outperformed in most measurements comparing supervised machine learning methods such as RF, GBM, SVM, and KNN, both with and without augmented spectral datasets. For model training, a whole range of spectra wavenumbers ( $$320 \hbox { cm}^{-1}$$ to $$1650 \hbox { cm}^{-1}$$ ) as well as wavenumbers ( $$1078 \hbox { cm}^{-1}$$ and $$1582 \hbox { cm}^{-1}$$ ) only for fingerprint peak spectra were employed. The former led to highly accurate 0.9750 predictions in comparison to 0.4318 for the latter one. Finally, independent experimental spectra of SARS-CoV-2 Omicron variant were used in the model verification. Thus, DeepATsers can be considered a robust, generalized, and generative deep learning framework for 1D SERS spectral datasets of SARS-CoV-2.